Effect of Peanut (Arachis Hypogaea L.) on Dyslipidemia in Young Adult - Akter, Hasina; Jahan, Nasim; Sultana, Nayma (Journal of Bangladesh Society of Physiologist, 2015)
Background: Dyslipidemia is a major risk factor for cardiovascular disease. Lipid lowering drugs are available in modern medicine but prolong use of these drugs may produce some side effects. Peanut due to some of its active component can improve lipid profile. Objective: To observe the effects of peanut (Arachis hypogaea L.) on dyslipidemia in young adults. Methods: This prospective interventional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka between 1st July 2013 and 30th June 2014. For this purpose 30 dyslipidemic young adults of both sexes with aged 30 to 40 years were included in this study and they were selected from Out Patient Department of Medicine of Sir Salimullah Medical College and Mitford Hospital, Dhaka. They were studied three times i,e before supplementation with peanut (BSP), after 4 weeks supplementation with peanut (4 wks AP) and after 8 weeks supplementation with peanut (8 wks AP). For assessing lipid profile TAG, LDL-C, TC and HDL-C of all subjects were estimated by enzymatic method. The statistical analysis was done by using paired samplet test as applicable. Results: In this study, the mean serum TAG, LDL-C and TC levels were significantly decreased after 8 weeks supplementation with peanut in comparison to those of after 4 weeks and before supplementation with peanut. However, these levels were also decreased after 4 weeks supplementation than those of before supplementation but it was significant only for TC (p<0.05) and LDL-C (p<0.001). Whereas, the mean serum HDL-C level was significantly (p<0.001) increased after 8 weeks supplementation when compared to those of after 4 weeks and before supplementation of peanut. Conclusion: The present study revealed that, peanut (Arachis hypogaea L.) has effect on improvement of lipid profile by lowering serum TAG, LDL-C, TC levels and by increasing serum HDL-C level. This lipid lowering effects of peanut may be due to its high Mg+2 content and other active components of peanut. Bangladesh Soc Physiol. 2015, June; 10(1): 11-16